Structured lipids from virgin coconut oil as permeation enhancers and emollients in cosmetics / Salizatul Ilyana Ibrahim - Ibrahim, Salizatul Ilyana (Institute of Graduate Studies, UiTM, 2014)
The influence of novel triacylglycerols (TAGs) on the topical delivery of α-tocopherol and their role as emollients was investigated. For topical application, TAGs as enhancers were developed to improve the delivery of actives across the skin as the skin barrier limited their use. Medium chain triacylglycerols (MCTs) have previously been used as carriers and enhancers for fat soluble vitamins and other actives as they work efficiently in delivering the active through the skin by modifying properties of the stratum corneum (SC) barrier. However, little published data are available concerning the permeation and effects of MCTs following topical application. The first part of the study was aimed to: i) develop and validate an assay method for determining α-tocopherol in methanolic solution and rat skin extract; ii) develop and validate an assay method for determining fatty acids methyl esters using gas chromatography; and iii) validate the automated diffusion equipment for in vitro experiment.